AKR1C2 and AKR1C3 expression in adipose tissue: Association with body fat distribution and regulatory variants. (1st May 2021) - Ostinelli, Giada; Vijay, Jinchu; Vohl, Marie-Claude; Grundberg, Elin; Tchernof, Andre
Abstract: Background: Changes in androgen dynamics within adipose tissue have been proposed as modulators of body fat accumulation. In this context, AKR1C2 likely plays a significant role by inactivating 5α-dihydrotestosterone. Aim: To characterize AKR1C2 expression patterns across adipose depots and cell populations and to provide insight into the link with body fat distribution and genetic regulation. Methods: We used RNA sequencing data from severely obese patients to assess patterns of AKR1C2 and AKR1C3 expression in abdominal adipose tissue depots and cell fractions. We additionally used data from 856 women to assess AKR1C2 heritability and to link its expression in adipose tissue with body fat distribution. Further, we used public resources to study AKR1C2 genetic regulation as well as reference epigenome data for regulatory element profiling and functional interpretation of genetic data. Results: We found that mature adipocytes and adipocyte-committed adipocyte progenitor cells (APCs) had enriched expression of AKR1C2 . We found adipose tissue AKR1C2 and AKR1C3 expression to be significantly and positively associated with percentage trunk fat mass in women. We identified strong genetic regulation of AKR1C2 by rs28571848 and rs34477787 located on the binding sites of two nuclear transcription factors, namely retinoid acid-related orphan receptor alpha and the glucocorticoid receptor. Conclusion: We confirm the link between AKR1C2, adipogenic differentiation and adipose tissue distribution. We provide insight into genetic regulation of AKR1C2 by identifying regulatory variants mapping to binding sites for the glucocorticoid receptor and retinoid acid-related orphan receptor alpha which may in part mediate the effect of AKR1C2 expression on body fat distribution. Highlights: AKR1C2 is highly expressed in human mature adipocytes and adipocyte-committed adipocyte progenitor cells (APCs). AKR1C2 expression in subcutaneous adipose tissue is positively associated with trunk body fat mass in women. The retinoid acid-related orphan receptor alpha (RORA) and the glucocorticoid receptor (GR) are likely to be important regulators of AKR1C2 expression in adipose tissue.